A patent review of cyclin-dependent kinase 7 (CDK7) inhibitors (2018-2022) - Kovalová, Markéta; Baraka, Joseph Peter; Mik, Václav; Jorda, Radek; Luo, Lei; Shao, Hao; Kryštof, Vladimír (Expert opinion on therapeutic patents, 2023)
INTRODUCTION: Cyclin-dependent kinase 7 (CDK7) is a member of the CDK family of serine/threonine protein kinases and participates in the regulation of the cell cycle and mRNA transcription. CDK7 is emerging as a possible drug target in oncology and six exciting drug candidates have already undergone early evaluation in clinical trials. AREAS COVERED: This review examines CDK7 inhibitors as anticancer drugs reported in patents published in the online databases of the World Intellectual Property Organization and European Patent Office in the 2018-2022 period. This review provides an overview of available inhibitors, including their chemical structures, biochemical profile and stage of development. EXPERT OPINION: Small-molecule CDK7 inhibitors represent attractive pharmacological modalities for the treatment of various cancer types. Highly potent and selective inhibitors have been discovered and many of them show promising results in several preclinical cancer models. Developed compounds act on the kinase by various mechanisms, including traditional ATP competition, irreversible binding to tractable cysteine 312 outside the active site of CDK7, and induced protein degradation by proteolysis targeting chimeras. Ongoing preclinical research and clinical trials should reveal which strategy will provide the highest benefits.
Keywords: Humans; inhibitory proteinkinas; CAK; Cyclin-Dependent Kinase-Activating Kinase; cyklin-dependentní kinasy; Cyclin-Dependent Kinases; PROTAC; protein-serin-threoninkinasy; cancer; cyclin-dependent kinase 7; lidé; Patents as Topic; Protein Kinase Inhibitors; patenty jako téma; Protein Serine-Threonine Kinases; kinasa aktivující cyklin dependentní kinasy; kinase inhibitor; Neoplasms; nádory